Qualitative Study: Management of the Prolanis Diabetes Mellitus Program at the Kramatsari Community Health Center in Pekalongan City - Rahmatika, Shilnia; Falla, Aisya Nurul; Aini, Fadhilla Anisa Nur; Azmi, Zubaidah Tsania Ulul; Mastuti, Dewi Nugrahaeni Restu; Indriyani, Yulis (International Journal of Health and Information System, 2025)
Diabetes mellitus (DM) is a chronic disease that has a significant impact across the country and is a major focus of treatment in primary health care. This study aims to assess the implementation of the chronic disease management program (PROLANIS) related to DM at the Kramatsari Community Health Center in Pekalongan City. The method used was descriptive qualitative, with in-depth interviews conducted with four informants: the head of the community health center, the community health center coordinator, and two program participants. Data analysis was conducted using a thematic approach based on the Miles and Huberman model, which includes data reduction, presentation, and conclusion drawing, along with source triangulation to increase data validity. The findings of this study indicate that PROLANIS has successfully increased patient awareness of a healthy lifestyle, adherence to treatment, and control of blood pressure and blood sugar. However, several challenges remain, such as long queues, mobility difficulties for elderly participants, and limited access to administrative documents. Recommendations include the need for intersectoral collaboration and the provision of mobile health units to reach elderly participants. Overall, although this program has had a positive impact, improvements in infrastructure, documentation systems, and community support are needed to ensure the program's benefits are sustainable and equitable.